Resin composition, pellet, molded article, and composite

The resin composition, featuring a polyalkylene terephthalate resin with high terminal vinyl and carboxyl groups, and fibrous reinforcement, addresses the need for strong adhesion to silicone adhesives while preserving mechanical integrity.

JP2025063759APending Publication Date: 2025-04-16MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023173207
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

There is a need for a resin composition that provides a molded product with excellent adhesion strength to other members using silicone adhesives, while maintaining mechanical strength.

Method used

A resin composition containing 10 to 150 parts by mass of a fibrous reinforcement material and a polyalkylene terephthalate resin with a high concentration of terminal vinyl groups (12 to 30 μmol/g) and terminal carboxyl groups (30 to 100 μmol/g), which includes a polybutylene terephthalate resin and has an intrinsic viscosity of 0.60 to 1.30 dL/g.

Benefits of technology

The resin composition achieves high adhesive strength with silicone adhesives and maintains mechanical strength, enabling the production of molded products and composites with enhanced bonding properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063759000001
    Figure 2025063759000001
  • Figure 2025063759000002
    Figure 2025063759000002
  • Figure 2025063759000003
    Figure 2025063759000003
Patent Text Reader

Abstract

To provide a resin composition that maintains mechanical strength while enabling the production of molded articles with excellent bonding strength to other members using a silicone adhesive, as well as pellets, molded articles, and composites.SOLUTION: A resin composition comprises 10 to 150 pts.mass of fibrous reinforcing material relative to 100 pts.mass of polyalkylene terephthalate resin, wherein the terminal vinyl group concentration of the polyalkylene terephthalate resin is 12 to 30 μmol / g.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a pellet, a molded article, and a composite, and in particular to a resin composition containing a polyalkylene terephthalate resin. [Background technology]

[0002] Polyalkylene terephthalate resins, typified by polybutylene terephthalate resin and polyethylene terephthalate resin, are characterized by excellent mechanical properties, electrical properties, processing properties, and the like, and are widely used in various applications (Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2019 / 217680 [Patent Document 2] JP 2018-203932 A [Patent Document 3] International Publication No. 2020 / 246335 Summary of the Invention [Problem to be solved by the invention]

[0004] Here, for a resin composition containing a polyalkylene terephthalate resin, high adhesive strength with other members is required depending on the application. In particular, a resin composition capable of providing a molded product having excellent adhesive strength with other members using a silicone adhesive while maintaining mechanical strength is required. The present invention has an object to solve the above problems, and to provide a resin composition capable of providing a molded article having excellent adhesive strength to other members using a silicone-based adhesive while maintaining mechanical strength, as well as pellets, a molded article, and a composite. [Means for solving the problem]

[0005] In view of the above problems, the present inventors have conducted studies and found that the above problems can be solved by using a polyalkylene terephthalate resin having a high concentration of terminal vinyl groups. Specifically, the above problems were solved by the following means. <1> A resin composition comprising 10 to 150 parts by mass of a fibrous reinforcing material per 100 parts by mass of a polyalkylene terephthalate resin, the polyalkylene terephthalate resin having a terminal vinyl group concentration of 12 to 30 μmol / g. <2> The polyalkylene terephthalate resin has a terminal carboxyl group concentration of 30 to 100 μmol / g. <1> The resin composition according to claim 1. <3> The polyalkylene terephthalate resin comprises a polybutylene terephthalate resin. <1> or <2> The resin composition according to claim 1. <4> The polyalkylene terephthalate resin has an intrinsic viscosity of 0.60 to 1.30 dL / g. <1> ~ <3> 10. The resin composition according to claim 9 . <5> The polyalkylene terephthalate resin contains recycled products. <1> ~ <4> 10. The resin composition according to claim 9 . <6> The polyalkylene terephthalate resin has a terminal carboxyl group concentration of 30 to 100 μmol / g; the polyalkylene terephthalate resin comprises a polybutylene terephthalate resin; The polyalkylene terephthalate resin has an intrinsic viscosity of 0.60 to 1.30 dL / g; The polyalkylene terephthalate resin contains recycled products. <1> ~ <5> 10. The resin composition according to claim 9 . <7> For use with silicone adhesives. <1> ~ <6> 10. The resin composition according to claim 9 . <8> <1> ~ <7> 2. A pellet of the resin composition according to claim 1. <9> <1> ~ <7> 2. A molded article molded from the resin composition according to claim 1. <10> <8> A molded article molded from the pellets according to claim 1. <11> <9> or <10> and an adhesive layer, the adhesive layer comprising a silicone-based adhesive. Effect of the Invention

[0006] The present invention makes it possible to provide a resin composition capable of providing a molded article that has excellent adhesive strength to other members using a silicone-based adhesive while maintaining mechanical strength, as well as pellets, molded articles, and composites. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified. If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated.

[0008] The resin composition of the present embodiment is characterized in that it contains 10 to 150 parts by mass of a fibrous reinforcing material relative to 100 parts by mass of a polyalkylene terephthalate resin, and the terminal vinyl group concentration of the polyalkylene terephthalate resin is 12 to 30 μmol / g. By adopting such a constitution, a resin composition capable of providing a molded product having high adhesive strength to a silicone adhesive can be obtained. In the present embodiment, it is presumed that the use of a polyalkylene terephthalate resin having a high concentration of terminal vinyl groups improves the adhesive strength to the silicone adhesive, that is, it is presumed that the vinyl groups react with the silicone adhesive. The details of this embodiment will be described below.

[0009] <Polyalkylene terephthalate resin> The resin composition of the present embodiment contains a polyalkylene terephthalate resin having a terminal vinyl group concentration of 12 to 30 μmol / g. By using such a polyalkylene terephthalate resin, the adhesive strength with a silicone adhesive can be increased.

[0010] The terminal vinyl group concentration of the polyalkylene terephthalate resin is preferably 13 μmol / g or more, more preferably 14 μmol / g or more, even more preferably 15 μmol / g or more, even more preferably 17 μmol / g or more, and is preferably 28 μmol / g or less, more preferably 24 μmol / g or less, and even more preferably 20 μmol / g or less. By making it equal to or more than the lower limit, the adhesive strength to the adhesive tends to be more excellent. Also, by making it equal to or less than the upper limit, the viscosity increase suppression effect and the color tone deterioration suppression effect tend to be more improved. When the resin composition of the present embodiment contains two or more types of polyalkylene terephthalate resins, the terminal vinyl group concentration of the mixture is preferably within the above range. The terminal vinyl group concentration of the polyalkylene terephthalate resin is measured according to the description in the Examples section described later.

[0011] Such a polyalkylene terephthalate resin having a high concentration of terminal vinyl groups can be obtained from recycled polyalkylene terephthalate resins, particularly recycled products derived from connector parts. Furthermore, the terminal vinyl group concentration of the polyalkylene terephthalate resin can also be increased by increasing the number of times the polyalkylene terephthalate resin is subjected to heat history, for example, by increasing the number of times it is melt-kneaded.

[0012] In the resin composition of the present embodiment, the terminal carboxyl group concentration of the polyalkylene terephthalate resin is preferably 100 μmol / g or less, more preferably 80 μmol / g or less, and even more preferably 65 μmol / g or less, and is preferably 30 μmol / g or more, more preferably 35 μmol / g or more, even more preferably 40 μmol / g or more, even more preferably 45 μmol / g or more, even more preferably 50 μmol / g or more, and even more preferably 55 μmol / g or more. By making it equal to or less than the upper limit, the hydrolysis resistance tends to be further improved. Also, by making it equal to or more than the lower limit, the adhesive strength to the adhesive tends to be further improved. When the resin composition of the present embodiment contains two or more types of polyalkylene terephthalate resins, the terminal carboxyl group concentration of the mixture is preferably within the above range. The terminal carboxyl group concentration of the polyalkylene terephthalate resin is measured according to the description in the Examples section described later. A polyalkylene terephthalate resin having such a concentration of terminal carboxyl groups can be obtained, for example, by subjecting the resin to a thermal history of a temperature equal to or higher than the melting point, such as by melt kneading.

[0013] In the resin composition of this embodiment, the terminal hydroxyl group concentration of the polyalkylene terephthalate resin is preferably 97 μmol / g or less, more preferably 90 μmol / g or less, even more preferably 80 μmol / g or less, even more preferably 70 μmol / g or less, and preferably 30 μmol / g or more, more preferably 35 μmol / g or more, even more preferably 40 μmol / g or more, even more preferably 50 μmol / g or more, and even more preferably 61 μmol / g or more. By making it below the upper limit, the transesterification reaction is suppressed during melt-kneading with other resins such as polycarbonate, and the molding cycle tends to be faster. Also, by making it above the lower limit, the adhesive strength to the adhesive tends to be further improved.

[0014] When the resin composition of the present embodiment contains two or more types of polyalkylene terephthalate resins, the terminal hydroxy group concentration of the mixture is preferably within the above range. The terminal hydroxyl group concentration of the polyalkylene terephthalate resin is measured according to the description in the Examples section described later. A polyalkylene terephthalate resin having such a terminal hydroxyl group concentration can be obtained by, for example, subjecting the resin to a thermal history of a temperature equal to or higher than the melting point, such as by melt kneading.

[0015] The intrinsic viscosity of the polyalkylene terephthalate resin is preferably 0.60 dL / g or more, more preferably 0.65 dL / g or more, and even more preferably 0.70 dL / g or more. By making it equal to or more than the lower limit, there is a tendency that the deterioration of physical properties such as strength can be effectively suppressed. In addition, the intrinsic viscosity of the polyalkylene terephthalate resin is preferably 1.30 dL / g or less, more preferably 1.10 dL / g or less, even more preferably 1.00 dL / g or less, even more preferably 0.90 dL / g or less, even more preferably 0.81 dL / g or less, and even more preferably 0.77 dL / g or less. By making it equal to or less than the upper limit, there is a tendency that the deterioration of fluidity can be effectively suppressed.

[0016] The intrinsic viscosity is measured by the following method. Polyalkylene terephthalate resin pellets are dissolved in a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (mass ratio 1 / 1) by stirring at 110°C for 1 hour to a concentration of 1.00 g / dL. The solution is then cooled to 30°C. The time it takes for the sample solution and the solvent alone to fall at 30°C is measured using a fully automatic solution viscometer, and the intrinsic viscosity is calculated using the formula: Intrinsic viscosity=((1+4K H η sp ) 0.5 -1) / (2K H C) Here, η sp= η / η0-1, where η is the time it takes for the sample solution to fall, η0 is the time it takes for the solvent alone to fall, C is the concentration of the sample solution (g / dL), and K H is Huggins' constant. K H was set to 0.33. The fully automatic solution viscometer used is a product of Shibayama Scientific Co., Ltd. When the resin composition of the present embodiment contains two or more types of polyalkylene terephthalate resins, the intrinsic viscosity is the intrinsic viscosity of the mixture.

[0017] The polyalkylene terephthalate resin is a polyester obtained by, for example, polycondensation of terephthalic acid as a dicarboxylic acid compound and a diol, and may be either a homopolyester or a copolyester.

[0018] As the dicarboxylic acid compound constituting the polyalkylene terephthalate resin, a terphthalic acid compound or an ester-forming derivative thereof is preferably used. Aromatic dicarboxylic acids other than terephthalic acid can also be used in combination. Examples of such dicarboxylic acids include isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-3,3'-dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, diphenylether-4,4'-dicarboxylic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, diphenylisopropylidene-4,4'-dicarboxylic acid, 1,2-bis(phenoxy)ethane-4,4'-dicarboxylic acid, anthracene-2,5-dicarboxylic acid, anthracene-2,6-dicarboxylic acid, p-terphenylene-4,4'-dicarboxylic acid, and pyridine-2,5-dicarboxylic acid. These can be used in the polycondensation reaction as ester-forming derivatives such as dimethyl esters in addition to free acids. Of the above, isophthalic acid or its ester-forming derivatives are particularly preferred.

[0019] In addition, one or more aliphatic dicarboxylic acids such as adipic acid, azelaic acid, dodecanedioic acid, and sebacic acid, and alicyclic dicarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid can be mixed and used in small amounts together with terephthalic acid and the above-mentioned aromatic dicarboxylic acids.

[0020] Examples of dihydroxy compounds constituting the polyalkylene terephthalate resin include aliphatic diols such as ethylene glycol, propylene glycol, butanediol, hexylene glycol, neopentyl glycol, 2-methylpropane-1,3-diol, diethylene glycol, and triethylene glycol, alicyclic diols such as cyclohexane-1,4-dimethanol, and mixtures thereof. Among these, butanediol and ethylene glycol are particularly preferred.

[0021] In addition, one or more long-chain diols having a molecular weight of 400 to 6,000, such as polyethylene glycol, poly-1,3-propylene glycol, polytetramethylene glycol, etc. may be copolymerized. In addition, aromatic diols such as hydroquinone, resorcinol, naphthalene diol, dihydroxydiphenyl ether, and 2,2-bis(4-hydroxyphenyl)propane may also be used.

[0022] In addition to the above-mentioned bifunctional monomers, a small amount of a trifunctional monomer such as trimellitic acid, trimesic acid, pyromellitic acid, pentaerythritol, or trimethylolpropane may be used in combination to introduce a branched structure, or a monofunctional compound such as a fatty acid may be used in combination to adjust the molecular weight.

[0023] The polyalkylene terephthalate resin is preferably one that is mainly composed of polycondensation of terephthalic acid and diol, i.e., one that is composed of this polycondensate in an amount of more than 50% by mass of the entire resin, preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, still more preferably 95% by mass or more, and even more preferably 99% by mass or more. The diol is preferably an aliphatic diol, more preferably 1,4-butanediol or ethylene glycol, and more preferably 1,4-butanediol.

[0024] The preferred polyalkylene terephthalate resin is one in which 95 mol % or more of the acid component is terephthalic acid and 95 mol % or more of the alcohol component is an aliphatic diol, and representative examples thereof are polybutylene terephthalate resin and polyethylene terephthalate resin. These are preferably close to homopolyesters, that is, 95 mol % or more of the entire resin is composed of terephthalic acid components and 1,4-butanediol or ethylene glycol components. The polyalkylene terephthalate resin is preferably a polybutylene terephthalate resin and / or a polyethylene terephthalate resin, more preferably a polybutylene terephthalate resin. Among them, the polyalkylene terephthalate resin preferably contains polybutylene terephthalate resin as a main component, and more than 50% by mass of the polyalkylene terephthalate resin is preferably polybutylene terephthalate resin. In this case, it is also preferable that the content of polyethylene terephthalate resin is less than 50% by mass.

[0025] Polybutylene terephthalate resin can be produced by batch or continuous melt polymerization of a dicarboxylic acid component mainly composed of terephthalic acid or an ester derivative thereof and a diol component mainly composed of 1,4-butanediol. After producing a low molecular weight polybutylene terephthalate resin by melt polymerization, the degree of polymerization (or molecular weight) can be increased to a desired value by further solid-phase polymerization under a nitrogen stream or reduced pressure.

[0026] The polybutylene terephthalate resin is preferably produced by a continuous melt polycondensation process of a dicarboxylic acid component mainly composed of terephthalic acid and a diol component mainly composed of 1,4-butanediol.

[0027] The catalyst used in carrying out the esterification reaction may be a conventionally known catalyst, and examples thereof include titanium compounds, tin compounds, magnesium compounds, calcium compounds, etc. Among these, titanium compounds are particularly preferred. Specific examples of titanium compounds as esterification catalysts include titanium alcoholates such as tetramethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate, and titanium phenolates such as tetraphenyl titanate.

[0028] The polybutylene terephthalate resin may be a polybutylene terephthalate resin modified by copolymerization (hereinafter, also referred to as a "modified polybutylene terephthalate resin"), and specific preferred copolymers include polyester ether resins copolymerized with polyalkylene glycols (particularly polytetramethylene glycol), dimer acid copolymerized polybutylene terephthalate resins, and isophthalic acid copolymerized polybutylene terephthalate resins.

[0029] When a polyester ether resin copolymerized with polytetramethylene glycol is used as the modified polybutylene terephthalate resin, the proportion of the tetramethylene glycol component in the copolymer is preferably 3 to 40 mass%, more preferably 5 to 30 mass%, and even more preferably 10 to 25 mass%. When a dimer acid copolymerized polybutylene terephthalate resin is used as the modified polybutylene terephthalate resin, the proportion of the dimer acid component in the total carboxylic acid components is preferably 0.5 to 30 mol %, more preferably 1 to 20 mol %, and even more preferably 3 to 15 mol %, in terms of carboxylic acid groups. When an isophthalic acid copolymerized polybutylene terephthalate resin is used as the modified polybutylene terephthalate resin, the proportion of isophthalic acid components in all carboxylic acid components is preferably 1 to 30 mol %, more preferably 1 to 20 mol %, and even more preferably 3 to 15 mol %, in terms of carboxylic acid groups. Among the modified polybutylene terephthalate resins, polyester ether resins copolymerized with polytetramethylene glycol and isophthalic acid copolymerized polybutylene terephthalate resins are preferred.

[0030] The melting point (Tm) of the polyalkylene terephthalate resin used in this embodiment measured according to DSC is preferably 200°C or higher, more preferably 205°C or higher, even more preferably 210°C or higher, even more preferably 215°C or higher, even more preferably 220°C or higher, and preferably 280°C or lower, more preferably 270°C or lower, even more preferably 260°C or lower, even more preferably 250°C or lower, and even more preferably 240°C or lower. By making it equal to or higher than the lower limit, the heat resistance tends to be further improved. Also, by making it equal to or lower than the upper limit, the molding cycle can be shortened. When the resin composition of the present embodiment contains two or more polyalkylene terephthalate resins, the melting point is the melting point of the mixture. When multiple melting point peaks are detected, at least one of the multiple melting points may be included in the range above the lower limit and below the upper limit, but it is preferable that the component with the highest content among the multiple melting points is included in the range above the lower limit and below the upper limit, and it is more preferable that all of the multiple melting points are included in the range above the lower limit and below the upper limit.

[0031] The crystallization temperature (Tc) of the polyalkylene terephthalate resin used in this embodiment measured according to DSC is preferably 130°C or higher, more preferably 145°C or higher, even more preferably 160°C or higher, even more preferably 170°C or higher, even more preferably 180°C or higher, even more preferably 185°C or higher, and preferably 240°C or lower, more preferably 220°C or lower, even more preferably 210°C or lower, even more preferably 200°C or lower, and even more preferably 190°C or lower. By setting it to the lower limit or higher, the solidification speed can be improved and the molding cycle can be accelerated. Also, by setting it to the upper limit or lower, the appearance of the molded product tends to be improved. When the resin composition of the present embodiment contains two or more polyalkylene terephthalate resins, the crystallization temperature is the crystallization temperature of the mixture.When multiple peaks of crystallization temperature are detected, at least one of the multiple crystallization temperatures may be included in the range of the lower limit or more and the upper limit or less, but among the multiple crystallization temperatures, it is preferable that the component with a large content is included in the range of the lower limit or more and the upper limit or less, and it is more preferable that all of the multiple crystallization temperatures are included in the range of the lower limit or more and the upper limit or less. The Tm and Tc of the polyalkylene terephthalate resin are measured according to the method described in the Examples below.

[0032] The polyalkylene terephthalate resin used in the present embodiment may be a recycled product. Examples of the recycled polyalkylene terephthalate resin include those obtained by material recycling in which molded products of recovered used polyalkylene terephthalate resin are crushed, washed, and reused, and those obtained by chemical recycling (chemical decomposition method). In this embodiment, material recycled products are preferred. In this embodiment, in particular, recycled polyalkylene terephthalate resins with many heat histories can be used. Heat histories include melt kneading, and thermoforming such as injection molding and extrusion molding. In this embodiment, polyalkylene terephthalate resins with 3 to 10 heat histories can be used. Examples of such recycled products include connectors, home appliances, toothbrushes, textiles, miscellaneous goods, automobile parts, films, tubes, and other extruded parts.

[0033] Polyalkylene terephthalate resins, particularly recycled polyalkylene terephthalate resins, may contain metal elements as impurities, which may come from reactors or cutters used in pulverization, pelletization, and the like.

[0034] The amount of aluminum element in the polyalkylene terephthalate resin used in this embodiment is preferably more than 1 μg / g, more preferably 2 μg / g or more, and preferably 150 μg / g or less, more preferably 100 μg / g or less, even more preferably 90 μg / g or less, even more preferably 80 μg / g or less, even more preferably 60 μg / g or less, even more preferably 40 μg / g or less, even more preferably 20 μg / g or less, and particularly more preferably 15 μg / g or less.

[0035] The amount of iron element in the polyalkylene terephthalate resin used in this embodiment is preferably more than 1 μg / g, more preferably 1.5 μg / g or more, even more preferably 2 μg / g or more, even more preferably 5 μg / g or more, and is preferably 150 μg / g or less, more preferably 100 μg / g or less, even more preferably 90 μg / g or less, even more preferably 80 μg / g or less. It is more preferably 60 μg / g or less, even more preferably 40 μg / g or less, even more preferably 20 μg / g or less, and particularly more preferably 10 μg / g or less. The amounts of iron element and aluminum element in the polyalkylene terephthalate resin are measured according to the method described in the Examples below.

[0036] The content of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) in the resin composition of this embodiment is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, and even more preferably 65% ​​by mass or more, based on 100% by mass of the resin composition. The content of the polyalkylene terephthalate resin (preferably polybutylene terephthalate resin) is preferably 85% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less. The resin composition of the present embodiment may contain only one type of polyalkylene terephthalate resin (preferably polybutylene terephthalate resin), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0037] <Fiber reinforcement> The resin composition of the present embodiment contains a fibrous reinforcing material. By containing the fibrous reinforcing material, the mechanical strength of the resulting molded product can be increased. The fibrous reinforcing material is a fibrous material that has the effect of improving the mechanical properties of the resin composition obtained by blending it with a resin, and a wide range of commonly used fibrous reinforcing materials for plastics can be used.

[0038] Raw materials for the fibrous reinforcing material include inorganic substances such as glass, carbon (carbon fiber, etc.), alumina, boron, ceramics, and metals (steel, etc.), and organic substances such as plants (including kenaf, bamboo, etc.), aramid, polyoxymethylene, aromatic polyamide, polyparaphenylene benzobisoxazole, and ultra-high molecular weight polyethylene, with glass being preferred.

[0039] The glass fibers are selected from glass compositions such as A-glass, C-glass, E-glass, R-glass, D-glass, M-glass, and S-glass, with E-glass (alkali-free glass) being particularly preferred. Glass fiber refers to a fibrous material whose cross section cut perpendicularly to the length direction has a perfect circle or polygonal shape. The number average fiber diameter of the single fiber of the glass fiber is usually 1 to 25 μm, preferably 5 to 17 μm. By making the number average fiber diameter 1 μm or more, the moldability of the resin composition tends to be improved. By making the number average fiber diameter 25 μm or less, the appearance of the obtained structure tends to be improved, and the reinforcing effect also tends to be improved. The glass fiber may be a single fiber or a plurality of single fibers twisted together. The form of the glass fiber may be any of glass rovings obtained by continuously winding single fibers or multiple twisted fibers, chopped strands cut to a length of 1 to 10 mm (i.e., glass fibers having a number average fiber length of 1 to 10 mm), milled fibers pulverized to a length of about 10 to 500 μm (i.e., glass fibers having a number average fiber length of 10 to 500 μm), etc., but chopped strands cut to a length of 1 to 10 mm are preferred. Glass fibers of different forms can also be used in combination. Glass fibers having an irregular cross-sectional shape are also preferred. The irregular cross-sectional shape has an aspect ratio, which is the long axis / short axis ratio of a cross section perpendicular to the longitudinal direction of the fiber, of, for example, 1.5 to 10, preferably 2.5 to 10, more preferably 2.5 to 8, and even more preferably 2.5 to 5.

[0040] The glass fiber may be surface-treated with, for example, a silane-based compound, an epoxy-based compound, a urethane-based compound, or the like, or may be oxidized, in order to improve its affinity with the resin component, as long as this does not significantly impair the properties of the resin composition in this embodiment.

[0041] The content of the fibrous reinforcing material (preferably glass fiber) in the resin composition of this embodiment is 10 parts by mass or more, preferably 15 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 35 parts by mass or more, relative to 100 parts by mass of the polyalkylene terephthalate resin. By making it equal to or more than the lower limit, the mechanical strength of the obtained molded article tends to be further increased. In addition, the content of the fibrous reinforcing material (preferably glass fiber) is 150 parts by mass or less, preferably 140 parts by mass or less, more preferably 120 parts by mass or less, more preferably 100 parts by mass or less, more preferably 80 parts by mass or less, more preferably 70 parts by mass or less, more preferably 60 parts by mass or less, more preferably 50 parts by mass or less, and may be 45 parts by mass or less, relative to 100 parts by mass of the polyalkylene terephthalate resin. By making it equal to or less than the upper limit, the appearance of the obtained molded article tends to be further improved.

[0042] The content of the fibrous reinforcing material (preferably glass fiber) in the resin composition in this embodiment is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and even more preferably 25% by mass or more, in 100% by mass of the resin composition. The content of the fibrous reinforcing material (preferably glass fiber) in the resin composition is more preferably 60% by mass or less, even more preferably 55% by mass or less, even more preferably 45% by mass or less, even more preferably 40% by mass or less, and even more preferably 35% by mass or less. By making it equal to or more than the lower limit, the mechanical strength tends to be further increased. By making it equal to or less than the upper limit, the appearance of the obtained molded product tends to be further improved. The resin composition in this embodiment may contain only one type of fibrous reinforcing material (preferably glass fiber), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0043] <Reactive compounds> The resin composition of the present embodiment may contain a reactive compound. The reactive compound is preferably at least one selected from the group consisting of a carbodiimide compound, an epoxy compound, a compound having an oxazoline group (ring), a compound having an oxazine group (ring), a compound having a carboxylic acid, and a compound having an amide group, and is particularly preferably an epoxy compound, since it tends to improve hydrolysis resistance and adhesion to a silicone adhesive. The epoxy compound may be a monofunctional epoxy compound or a polyfunctional epoxy compound, but is preferably a polyfunctional epoxy compound.As the polyfunctional epoxy compound, for example, bisphenol A type epoxy compound, bisphenol F type epoxy compound, resorcin type epoxy compound, novolac type epoxy compound, alicyclic compound type diepoxy compound, glycidyl ethers, epoxidized polybutadiene, more specifically, bisphenol A type epoxy compound, bisphenol F type epoxy compound, resorcin type epoxy compound, novolac type epoxy compound, vinylcyclohexene dioxide, dicyclopentadiene oxide, and other alicyclic compound type epoxy compounds can be preferably used.Among them, bisphenol A type epoxy compound and novolac type epoxy compound are preferred. The epoxy compound may also be a copolymer containing a glycidyl group-containing compound as a constituent component, such as a copolymer of a glycidyl ester of an α,β-unsaturated acid and one or more monomers selected from the group consisting of an α-olefin, acrylic acid, an acrylic acid ester, methacrylic acid, a methacrylic acid ester, and styrene. The epoxy compound is preferably a copolymer of an epoxy group-containing monomer and a styrene-based monomer, and may be a copolymer of other copolymerizable monomers. Examples of the styrene-based monomer constituting the copolymer of an epoxy group-containing monomer and a styrene-based monomer include, for example, glycidyl (meth)acrylate and glycidyl itaconate, and preferably glycidyl methacrylate and glycidyl acrylate, and particularly preferably glycidyl methacrylate. Examples of the styrene-based monomer include styrene, α-methylstyrene, p-methylstyrene, vinylxylene, ethylstyrene, dimethylstyrene, p-tert-butylstyrene, vinylnaphthalene, methoxystyrene, monobromostyrene, dibromostyrene, fluorostyrene, and tribromostyrene, and more preferably styrene and α-methylstyrene, and particularly preferably styrene. Specific examples of copolymers of epoxy group-containing monomers and styrene-based monomers include glycidyl (meth)acrylate-styrene copolymers and glycidyl (meth)acrylate-styrene-methyl (meth)acrylate, etc., which tend to improve adhesion to adhesives and are therefore particularly preferred.

[0044] The epoxy equivalent of the epoxy compound used in the present embodiment is preferably 100 g / eq or more, more preferably 150 g / eq or more, and is preferably 1000 g / eq or less, more preferably 300 g / eq or less, and even more preferably 250 g / eq or less. When the resin composition of the present embodiment contains two or more kinds of epoxy compounds, the epoxy equivalent is a value (weighted average value) obtained by multiplying the epoxy equivalent of each epoxy compound by the mass fraction of each epoxy compound.

[0045] In addition to the above, the reactive compounds can be found in paragraphs 0038 to 0050 of JP-A-2020-199755 and paragraph 0043 of JP-A-2020-125468, the contents of which are incorporated herein by reference.

[0046] When the resin composition of the present embodiment contains a reactive compound, the content is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.1 parts by mass or more, and even more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the polyalkylene terephthalate resin. The upper limit of the content of the reactive compound is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 7.0 parts by mass or less, and even more preferably 2.0 parts by mass or less, relative to 100 parts by mass of the polyalkylene terephthalate resin. The resin composition of the present embodiment may contain only one type of reactive compound, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0047] <Stabilizer> The resin composition of the present embodiment may contain a stabilizer (a light stabilizer and / or a heat stabilizer). The stabilizer preferably contains one or more compounds selected from the group consisting of thioether compounds, hindered phenol compounds, and phosphite compounds, and more preferably a hindered phenol compound. In the present embodiment, it is also preferable to use two or more of the thioether-based compounds, the hindered phenol-based compounds, and the phosphite-based compounds in combination as necessary.

[0048] As the thioether-based compound, any conventionally known sulfur atom-containing compound can be used, and among them, thioethers are preferred. By including the thioether-based compound in the resin composition of the present embodiment, the appearance of the molded product tends to be improved and the thermal stability tends to be improved. Specific examples include didodecylthiodipropionate, ditetradecylthiodipropionate, dioctadecylthiodipropionate, pentaerythritol tetrakis(3-dodecylthiopropionate), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-(dodecylthio)propionate], thiobis(N-phenyl-β-naphthylamine), 2-mercaptobenzothiazole, 2-mercaptobenzimidazole, tetramethylthiuram monosulfide, tetramethylthiuram disulfide, nickel dibutyldithiocarbamate, nickel isopropylxanthate, and trilauryltrithiophosphite. Among these, 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-(dodecylthio)propionate] is preferable. Commercially available products include "Seenox 412S" manufactured by Shipro Chemical Co., Ltd. and "Adekastab AO-412S" manufactured by ADEKA Corporation.

[0049] Examples of hindered phenol compounds include pentaerythritol tetrakis (3-(3,5-di-t-butyl-4-hydroxyphenyl) propionate), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, thiodiethylene bis (3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), pentaerythritol tetrakis (3-(3,5-di-neopentyl-4-hydroxyphenyl) propionate), 1,3,5-trimethyl-2,4,6-tris (3,5-di-tert-butyl-4-hydroxybenzyl) benzene, etc. Among these, pentaerythritol tetrakis (3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate are preferred. Commercially available products include those manufactured by ADEKA Corporation under the trade names "ADEKA STAB AO-60" and "ADEKA STAB AO-330."

[0050] The phosphite compound is preferably a compound represented by the formula: R 2 OP(OR 3 )(OR 4 ) (In the formula, R 2 , R 3 and R 4 are each a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, or an aryl group having 6 to 30 carbon atoms, and R 2 , R 3 and R 4 At least one of the groups is an aryl group having 6 to 30 carbon atoms.) Examples of the compound include compounds represented by the following formula: Examples of the phosphite compound include triphenyl phosphite, tris(nonylphenyl)phosphite, dilauryl hydrogen phosphite, triethyl phosphite, tridecyl phosphite, tris(2-ethylhexyl)phosphite, tris(tridecyl)phosphite, tristearyl phosphite, diphenyl monodecyl phosphite, monophenyl didecyl phosphite, diphenyl mono(tridecyl)phosphite, tetraphenyl dipropylene glycol diphosphite, tetraphenyl tetra(tridecyl)pentaerythritol tetraphosphite, hydrogenated bisphenol A phenol phosphite polymer, diphenyl hydrogen phosphite, 4,4'-butylidene-bis(3-methyl-6-tert-butylphenyl di(tridecyl)phosphite), tetra(tridecyl) 4,4'-isopropyl phosphite, tetra(tridecyl) ... propylidenediphenyl diphosphite, bis(tridecyl)pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, dilauryl pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, tris(4-tert-butylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, hydrogenated bisphenol A pentaerythritol phosphite polymer, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, and the like. Among these, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite is preferable. An example of a commercially available product is "ADEKA STAB PEP-36" manufactured by ADEKA Corporation.

[0051] Other examples of stabilizers include the following: JP 2021-063196 A, paragraphs 0067 to 0075; JP 2018-070722 A, paragraphs 0046 to 0057; JP 2019-056035 A, paragraphs 0030 to 0037; and WO 2017 / 038949 A, paragraphs 0066 to 0078. The contents of these are incorporated herein by reference.

[0052] The content of the stabilizer in the resin composition of the present embodiment is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the polyalkylene terephthalate resin. By making it equal to or more than the lower limit, the effect of suppressing thermal deterioration and oxidative deterioration of the resin during melt kneading, molding, and use as a molded body tends to be improved, and heat resistance tends to be improved. In addition, the upper limit of the content of the stabilizer is preferably 1.0 parts by mass or less, more preferably 0.8 parts by mass or less, more preferably 0.6 parts by mass or less, even more preferably 0.5 parts by mass or less, and even more preferably 0.4 parts by mass or less, relative to 100 parts by mass of the polyalkylene terephthalate resin. By making it equal to or less than the upper limit, it tends to be possible to effectively suppress adverse effects on appearance and physical properties due to aggregation of additives such as stabilizers, and it tends to be possible to suppress discoloration of the resin composition. The resin composition of the present embodiment may contain only one type of stabilizer, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0053] <Other ingredients> The resin composition of the present embodiment may contain other components in addition to the above-mentioned components as necessary, as long as the desired physical properties are not significantly impaired. The other components may be contained alone or in any combination and ratio of two or more. Examples of other components include thermoplastic resins other than polyalkylene terephthalate resins, resin additives, and fillers other than the above-mentioned fibrous reinforcing materials. Specific examples of the resin additives include flame retardants, flame retardant assistants, colorants (pigments, dyes), nucleating agents, antistatic agents, antifogging agents, antiblocking agents, flow improvers, plasticizers, and dispersants. The total amount of these other components is preferably 0% by mass or more and less than 10% by mass, more preferably 0% by mass or more and less than 5% by mass, and even more preferably 0% by mass or more and less than 3% by mass, based on 100% by mass of the resin composition. In the resin composition of the present embodiment, the total amount of the polyalkylene terephthalate resin, the fibrous reinforcing material, and any other components blended as necessary is 100 mass %. In the resin composition of this embodiment, the polyalkylene terephthalate resin, the fibrous reinforcing material, the reactive compound, and the stabilizer preferably account for 90 mass% or more of the resin composition, more preferably 95 mass% or more, and even more preferably 97 mass% or more, and may even be 100 mass%.

[0054] <Physical properties of resin composition> The resin composition of this embodiment has a melt volume rate (MVR) of 4 cm at 250°C and a load of 5 kgf. 3 / min or more is preferable, and 7cm 3 / min or more is preferable, and 10 cm 3 More preferably, the rate is 15 cm / min or more. 3 / min or more is more preferable, and 25 cm 3 / min or more is even more preferable, 3 / min or more, and even more preferably 35 cm 3 / min or more, and 3 / min or less is preferable, and 3 / min or less is more preferable, and 3 More preferably, the speed is 60 cm / min or less. 3 More preferably, it is 50 cm / min or less. 3 / min or less is even more preferable, 3 More preferably, the average is 39 cm / min or less. 3 / min or less, and even more preferably 38 cm 3 By setting the melt flow rate to the above lower limit or more, the flowability in the molten state is improved, and the moldability tends to be excellent. By setting the melt flow rate to the above upper limit or less, the mechanical properties such as tensile strength tend to be excellent.

[0055] The resin composition of this embodiment is molded into an ISO test piece (4 mm thick) and has a tensile modulus of elasticity measured according to ISO527-1 and ISO527-2 of preferably 5000 MPa or more, more preferably 6000 MPa or more, even more preferably 7000 MPa or more, even more preferably 8000 MPa or more, and even more preferably 9000 MPa or more. The upper limit is not particularly set, but even if it is, for example, 100,000 MPa or less, the required performance is sufficiently satisfied. By making it equal to or greater than the lower limit, the rigidity of the molded article obtained from the resin composition is improved, and the molded article can be made thinner and lighter.

[0056] The resin composition of this embodiment is molded into an ISO test piece (4 mm thick) and has a tensile strength of preferably 70 MPa or more, more preferably 80 MPa or more, even more preferably 90 MPa or more, even more preferably 100 MPa or more, and even more preferably 110 MPa or more, and although there is no particular upper limit, for example, even if it is 500 MPa or less, the required performance is sufficiently satisfied. By making it equal to or greater than the lower limit, the mechanical strength of the molded product tends to be excellent.

[0057] The resin composition of this embodiment is molded into an ISO test piece (4 mm thick) and the tensile breaking strain measured according to ISO527-1 and ISO527-2 is preferably 0.5% or more, more preferably 0.8% or more, even more preferably 1.0% or more, even more preferably 1.2% or more, and even more preferably 1.5% or more, and the upper limit is not particularly set, but even if it is 10% or less, the required performance is sufficiently satisfied. By making it equal to or more than the lower limit, the toughness of the molded product tends to be excellent.

[0058] <Method of producing resin composition> The resin composition of this embodiment can be produced by a conventional method for preparing a resin composition (e.g., pellets). Usually, each component and various additives added as desired are thoroughly mixed together and then melt-kneaded in a single-screw or twin-screw extruder. The resin composition of this embodiment can also be prepared without premixing each component, or by premixing only a portion of the components, feeding the mixture to an extruder using a feeder and melt-kneading it. A portion of the components, such as a colorant, may be melt-kneaded with a thermoplastic resin to prepare a master batch, and then the remaining components may be blended therewith and melt-kneaded. The fibrous reinforcing material is preferably fed from a side feeder midway through the cylinder of the extruder. The heating temperature during melt kneading can be appropriately selected from the range of 220 to 300°C. If the temperature is too high, decomposition gas is likely to be generated, which may cause opacity. Therefore, it is desirable to select a screw configuration that takes into consideration shear heat generation, etc. In order to suppress decomposition during kneading and molding in the subsequent process, it is desirable to use an antioxidant or heat stabilizer.

[0059] <Method of manufacturing molded products> The molded article of this embodiment is molded according to a known method. The manufacturing method of the molded product is not particularly limited, and any molding method generally used for resin compositions can be used. Examples of such molding methods include injection molding, ultra-high speed injection molding, injection compression molding, two-color molding, gas-assisted hollow molding, molding using a heat-insulating mold, molding using a rapid heating mold, foam molding (including supercritical fluid), insert molding, IMC (in-mold coating molding), extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, etc., and among these, injection molding is preferred. For details of the injection molding method, refer to paragraphs 0113 to 0116 of Japanese Patent No. 6183822, the contents of which are incorporated herein by reference. The mold temperature during molding such as injection molding is preferably 40 to 150°C.

[0060] <Complex> The molded article obtained by molding the resin composition of this embodiment can be bonded to the same material or another member via an adhesive to form a composite. That is, the composite of this embodiment includes the molded article of this embodiment and an adhesive layer. The adhesive layer includes an adhesive (preferably a silicone-based adhesive). Therefore, the resin composition, pellets, and molded article of this embodiment can be used for adhesive bonding (preferably for silicone-based adhesive bonding). The other materials include materials containing at least one of resin (thermoplastic resin, thermosetting resin), metal, and glass. An adhesive refers to a material that bonds two things together, and is usually a material that is not thermoplastic. Examples of the adhesive include silicone adhesives (unmodified silicone adhesives, modified silicone adhesives), epoxy adhesives, acrylic adhesives, urethane adhesives, polyester adhesives, etc., and silicone adhesives (unmodified silicone adhesives, modified silicone adhesives), epoxy adhesives, and urethane adhesives are preferred, with silicone adhesives being more preferred. Only one type of adhesive may be used, or two or more types may be mixed and used. The thickness of the adhesive layer is preferably 0.01 μm or more, more preferably 0.1 μm or more, and is preferably 10,000 μm or less, more preferably 5,000 μm or less.

[0061] <Application> The resin composition or pellets of the present embodiment are used as molded articles formed therefrom. The applications of the resin composition, pellets, or molded articles are not particularly limited, but are preferably for vehicle parts or electric / electronic parts. Vehicle parts include lamp housings, reflectors, bezels, extensions, connectors, ECU cases, housings for in-vehicle cameras and millimeter-wave radars, battery cases, and sensor housings. Examples of electric and electronic components include display devices such as personal computers, game consoles and televisions, printers, copy machines, scanners, fax machines, electronic organizers and PDAs, electronic desk calculators, electronic dictionaries, cameras, video cameras, mobile phones, battery packs, drives and readers for recording media, mice, numeric keypads, CD players, MD players, portable radio and audio players, housings, covers, keyboards, buttons, switch components, power meter cases, battery cases, battery transport trays, relays, sensors, actuators, terminal switches and grill cooking appliance parts. EXAMPLES

[0062] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.

[0063] 1.Raw materials The following raw materials were used: [Table 1]

[0064] Details of the above PBT-1 to PBT-4 are as follows. [Table 2]

[0065] <Intrinsic viscosity (IV)> The intrinsic viscosity was measured by the following method. Pellets of polyalkylene terephthalate resin were dissolved in a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (mass ratio 1 / 1) by stirring at 110°C for 1 hour to a concentration of 1.00 g / dL. The solution was then cooled to 30°C. Using a fully automatic solution viscometer, the number of seconds it took for the sample solution and the solvent alone to fall at 30°C were measured, and the intrinsic viscosity was calculated using the formula. The unit was dL / g. Intrinsic viscosity=((1+4K H η sp ) 0.5 -1) / (2K H C) Here, η sp = η / η0-1, where η is the time it takes for the sample solution to fall, η0 is the time it takes for the solvent alone to fall, C is the concentration of the sample solution (g / dL), and K H is Huggins' constant. K H was set to 0.33. The fully automatic solution viscometer used was a product of Shibayama Scientific Co., Ltd.

[0066] <Melting point (Tm) and crystallization temperature (Tc)> The melting point (Tm) and crystallization temperature (Tc) of the polyalkylene terephthalate resin were measured using a differential scanning calorimeter (DSC) based on JIS K7121. The temperature was raised from 40°C to 300°C at a heating rate of 20°C / min under a nitrogen atmosphere, and after holding at 300°C for 3 minutes, the temperature was lowered to 40°C at a heating rate of -20°C / min. This was defined as one cycle. The temperature of the maximum peak due to crystallization during cooling was defined as the crystallization temperature Tc. The melting point Tm was determined from the peak during melting. The unit is °C. The differential scanning calorimeter used was "DSC7020" manufactured by Hitachi High-Tech Science Corporation.

[0067] <ash content> The pellets were incinerated in an electric furnace at 500°C for 3 hours to burn off the resin component alone, and the ash content was measured based on the mass ratio to the residue. The ash content in the polyalkylene terephthalate resin was expressed in mass%. The electric furnace used was "Electric Muffle Furnace KM-28" manufactured by Toyo Seisakusho Co., Ltd.

[0068] <Terminal carboxyl group concentration> The terminal carboxyl group concentration of the polyalkylene terephthalate resin was determined by dissolving 0.5 g of the polyalkylene terephthalate resin in 25 mL of benzyl alcohol and titrating with a 0.01 mol / L benzyl alcohol solution of sodium hydroxide. The unit is μmol / g.

[0069] <Terminal hydroxyl group concentration> The terminal hydroxyl group concentration of polyalkylene terephthalate resin was measured by dissolving 25 mg of sample in a vial in 0.75 mL of a mixed solvent of deuterated chloroform / hexafluoroisopropanol (volume ratio: 7 / 3) containing a trace amount of TMS (tetramethylsilane), adding 25 μL of deuterated pyridine, and transferring to an NMR sample tube with an outer diameter of 5 mm. 1H NMR spectra were measured using a Bruke AVANCE NEO 600 spectrometer. The resonance frequency was 600, 1 MHz, the flip angle was 45°, the data acquisition time was 3 s, the pulse repetition time was 10 s, the number of accumulations was 16, and the temperature was 25°C. The unit is μmol / g.

[0070] <Terminal vinyl group concentration> The terminal vinyl group concentration of the polyalkylene terephthalate resin was measured under the same conditions as the terminal hydroxyl group concentration of the polyalkylene terephthalate resin, and the unit is μmol / g.

[0071] <Measurement of the amount of metal elements> Qualitative / semi-quantitative analysis of metal elements (Al, Fe) in polyalkylene terephthalate resin was performed by ICP emission spectrometry. In this case, 200 mg of sample was weighed out as pretreatment, and Kjeldahl wet decomposition (sulfuric acid / nitric acid, sulfuric acid / hydrogen peroxide) was performed, and the volume was adjusted to 50 mL. Then, ICP emission spectrometry was performed by acid concentration matching single point calibration method. The unit is shown in ppm by mass. ICP emission analysis was performed using a ThermoThromo Fisher Scientific "iCAP7600duoiCAP76000uo" by axial / radial photometry.

[0072] Examples 1 to 4, Comparative Examples 1 to 2 <Compound> The components shown in Table 1 were mixed uniformly in a tumbler mixer in the ratios shown in Table 3 (each component in Table 3 is shown in parts by mass), with the exception of the glass fibers. The mixture obtained was fed to a twin-screw extruder ("TEX30α" manufactured by Japan Steel Works, Ltd.) from the main feed port. The cylinder temperature setting of the first kneading section was set to 260°C, and the glass fibers were fed from a side feeder. The resin composition was melt-kneaded under conditions of a cylinder temperature setting of 220°C after the addition of the glass fibers and a screw rotation speed of 200 rpm, and was quenched in a water tank and pelletized using a pelletizer to obtain pellets of the resin composition.

[0073] <Measurement of MVR of resin composition> The melt volume rate of the pellets of the resin composition obtained above was measured in accordance with ISO1133 at 250°C and a load of 5 kgf. The unit is cm 3 / 10min.

[0074] <Adhesive strength> The resin pellets obtained above were dried at 120°C for 5 hours, and then ISO multipurpose test pieces (thickness 4 mm) were injection molded using an injection molding machine (Japan Steel Works, Ltd., "J-85AD-60H") under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C. A 20mm x 20mm square adhesive application area was created by attaching Nitto Corporation's NITOFLON adhesive tape (10mm wide x 0.18mm thick) to the chuck of the obtained ISO multipurpose test piece. A modified silicone adhesive (a one-part, room temperature curing adhesive whose main component is modified silicone polymer) was then applied to this area, and the chuck of another ISO multipurpose test piece of the same material was attached and fixed with a binder clip, and the adhesive was treated under the specified curing conditions to bond them together. A tensile test was performed using Shimadzu Corporation's AUTOGRAPH AGS-X 10kN at a tensile speed of 5mm / min, and the adhesive strength (unit: N) was measured.

[0075] <Tensile properties> The pellets obtained above were dried at 110°C for 5 hours, and then injection molded into 4 mm thick ISO test pieces using an injection molding machine (Japan Steel Works, Ltd., "J85AD") under conditions of a cylinder temperature of 250°C and a mold temperature of 80°C. For the ISO test pieces (4 mm thick) obtained above, the tensile modulus (unit: MPa), tensile strength (unit: MPa), and tensile breaking strain (unit: %) were measured in accordance with ISO527-1 and ISO527-2.

[0076] [Table 3]

[0077] As is clear from the above results, the molded articles formed from the resin compositions of the present invention had high adhesive strength to silicone adhesives (Examples 1 to 4), and were also excellent in various mechanical properties. In contrast, when a polyalkylene terephthalate resin with a low concentration of terminal vinyl groups was used (Comparative Examples 1 and 2), the adhesive strength to a silicone adhesive was low.

Claims

1. The composition contains 10 to 150 parts by mass of a fibrous reinforcing material relative to 100 parts by mass of a polyalkylene terephthalate resin, The polyalkylene terephthalate resin has a terminal vinyl group concentration of 12 to 30 μmol / g. Resin composition.

2. The polyalkylene terephthalate resin has a terminal carboxyl group concentration of 30 to 100 μmol / g. The resin composition according to claim 1.

3. The resin composition according to claim 1 or 2, wherein the polyalkylene terephthalate resin comprises a polybutylene terephthalate resin.

4. The resin composition according to claim 1 or 2, wherein the polyalkylene terephthalate resin has an intrinsic viscosity of 0.60 to 1.30 dL / g.

5. The resin composition according to claim 1 or 2, wherein the polyalkylene terephthalate resin comprises a recycled product.

6. The polyalkylene terephthalate resin has a terminal carboxyl group concentration of 30 to 100 μmol / g; the polyalkylene terephthalate resin comprises a polybutylene terephthalate resin; The polyalkylene terephthalate resin has an intrinsic viscosity of 0.60 to 1.30 dL / g; The resin composition of claim 1 , wherein the polyalkylene terephthalate resin comprises a recycled product.

7. The resin composition according to claim 1, 2 or 6, which is for use in bonding with a silicone adhesive.

8. A pellet of the resin composition according to claim 1, 2 or 6.

9. A molded article molded from the resin composition according to claim 1, 2 or 6.

10. A molded article made from the pellets according to claim 8.

11. A composite comprising the molded article of claim 9 and an adhesive layer, the adhesive layer comprising a silicone-based adhesive.

Citation Information

Patent Citations

  • Polybutylene terephthalate resin composition

    JP2018203932A

  • Reinforced polyester structural components

    WO2019217680A1

  • Resin composition and method for producing same

    WO2020246335A1